Pengaruh Citra Perusahaan, Relationship Marketing dan Kualitas Pelayanan Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan : Studi Pada Indomaret, Semolowaru, Sukolilo Surabaya - Dwi Rijal Giri Prabowo; Muhammad Irwan Susanto; Reyhan Arya Khahairudin Firdaus; Shofi Putri Julian (Jurnal Manajemen Bisnis Era Digital, 2024)
This study aims to analyze the effect of company image, relationship marketing, and service quality on customer loyalty at Indomaret Semolowaru, Surabaya. This research uses quantitative methods with data collection techniques through questionnaires distributed to 100 respondents. The results showed that corporate image, relationship marketing, and service quality have a positive influence on customer satisfaction. Customer satisfaction then has a positive influence on customer loyalty. The conclusion of this study is that corporate image, relationship marketing, and service quality are important factors that can increase customer loyalty at Indomaret Semolowaru, Surabaya. Indomaret needs to continue to improve service quality, build a positive corporate image, and establish good relationships with customers to increase customer loyalty.